The Effect of Technology-Enhanced Language Learning on Student Motivation and Engagement: A Comparative Study of the Social Environments of Online and Offline Learning - Bincar Nasution; Widya Pratiwi; Nur Latifah; Rizki Lestari; Suparjan Suparjan; Iswahyu Pranawukir; Hamirul Hamirul (Jurnal Mamangan, 2024)
The advent of the pandemic has prompted changes in the learning motivations of students. This investigation seeks to ascertain how students perceive the relative merits of online and offline modes of learning and their relationship with students' learning motivations. The research employed a qualitative approach with a descriptive methodology. This research design is descriptive with an interview approach, with the objective of eliciting students' perspectives on online and offline learning and their relationship to student learning motivation. The analysis of this study revealed a consensus among the respondents that online learning affords a greater sense of relaxation. Nevertheless, online learning is perceived as a source of boredom and lack of engagement. In contrast, offline learning is associated with a high level of motivation, particularly when students can learn with friends. This negative reaction manifests in students telling stories or engaging in other distracting activities when the teacher presents the learning material. Furthermore, students are easily bored during learning, suggesting that the relaxing experience of online learning has an adverse effect on their attention span in the traditional classroom setting. In light of the students’ perceptions, it is hoped that teachers will be able to create engaging offline learning environments and encourage more student activities with their peers.